Estudo das Características Psicométricas da Versão Portuguesa da Escala de Expressividade Emocional - Dinis, Alexandra (2011)
The Emotional Expressivity Scale (EES; Kring, Smith, & Neale, 1994) intended to assess the degree to which people outwardly display their emotions, regardless of emotional valence or channel of expression. This study presents the psychometric characteristics and the factorial structure of the Portuguese version. In a sample of 1008 subjects, students and general population, the results show that the scale as an accurate internal consistency and temporal stability. The factorial composition proved to be similar to the one found by original authors, showing clearly the existence of one-factor model. The convergent and discriminant validities as been studied through the analysis of the co-relationship with the anxiety, depression, and stress, emotional regulation, emotional intelligence, rumination, as well as the positive and negative affect. The results suggest that the Emotional Expressivity Scale is a useful and valid scale to assess emotional expressivity in the Portuguese population.